Employment Outcome among Cardiac Patients following Phase Two Intensive Outpatient Cardiac Rehabilitation Programme in a Local Heart Centre in Malaysia - Chai, Chau Chung; Leong, Be Kim; Liew, Lin Kiat; Chow, Kok Cheow (Hong Kong College of Cardiology, 2023)
Introduction: Cardiovascular disease is a crucial cause of morbidity and mortality in Malaysia, with impact on employment. Unemployment leads to both loss of productivity and increased socioeconomic burden to the society. There were limited local studies on employment outcome and barriers among cardiac patients in Malaysia.